Exploring the impact of self-confidence on students' mathematical representation skills - Putra, Fredi Ganda; Monalisa; Widyawati, Santi (Program Magister Pendidikan Matematika, Pascasarjana, Universitas Pasundan in collaboration with Asosiasi Guru Matematika Indonesia (AGMI) and Indonesian Mathematics Educators' Society (IMES), 2025)
This study investigates the influence of self-confidence on students' mathematical representation abilities, which are essential for interpreting and communicating mathematical ideas. Employing a comparative correlational design, the research involved eighth-grade students selected through a cluster random sampling method. The data were obtained using a self-confidence questionnaire and a mathematical representation test, both of which were validated for reliability and content relevance. Data analysis was conducted using statistical techniques to examine differences in students' representation skills based on their self-confidence levels. The findings reveal that students with higher self-confidence tend to demonstrate stronger abilities in representing mathematical concepts compared to those with moderate or low self-confidence. These students are more inclined to engage in problem-solving processes, utilize multiple forms of representation, and articulate their reasoning more effectively. The results support the idea that self-confidence plays a critical role in facilitating not only motivation and engagement but also cognitive performance in mathematics. This study underscores the importance of integrating strategies that nurture self-confidence within mathematics instruction. By doing so, educators can enhance students’ abilities to represent, interpret, and apply mathematical knowledge in meaningful ways. Encouraging a positive learning environment that values effort and supports student confidence may significantly contribute to overall mathematical proficiency.